Attributes and metrics for comparative quantification of disaster resilience across diverse performance mandates and standards of building. (January 2019) - Ladipo, Oluwateniola; Reichard, Georg; McCoy, Andrew; Pearce, Annie; Knox, Paul; Flint, Madeleine
Abstract: With the growing concern of climate change and more frequent and severe natural disaster events affecting the built environment, enhancing the performance and resilience of buildings has become increasingly vital. Stakeholders are seeking guidance towards improving both the individual performance of buildings and systems as well as their overall disaster resilience. Thus, they require tools that can comparatively evaluate technologies across multiple standards and qualities of construction in a consistent way. Such tools would be used as a means to make effective decisions based upon different performance metrics as they apply to a particular situation or context. However, neither common, succinct definitions nor metrics for evaluating both resilience and building performance across various construction standards exists, which makes conducting such assessments a considerably difficult task. Evaluating and comparing the performance and resilience levels of buildings and their systems in response to various natural disaster risks necessitates metrics that distinguish the contributing attributes for each aspect of performance and resilience. Consequently, such metrics then allow for benchmarking and comparisons between buildings and systems, and permit the quantification of potential improvements, or lack thereof, when implementing various building technologies in an effort to simultaneously increase performance and resilience. This paper addressed this need by demonstrating that attributes and corresponding metrics of disaster resilience for buildings can be consistently quantified by a function of Functionality and Time and subsequently used for disaster resilience assessments. A thematic analysis of a sample of relevant texts was conducted to validate the hypothesis theorized for measuring resilience. Highlights: Attributes and metrics of disaster resilient buildings. Resilience measurement function for building assessments. Evaluating and comparing the performance and resilience of buildings. Total resilience rating (TRR) factor for new and existing buildings.